Descripción de Thelastoma domesticus sp. nov. (Oxyurida, Thelastomatidae) parásita de ninfas Periplaneta americana (Blattodea, Blattidae) en Argentina - Camino, Nora Beatriz (2008)
Thelastoma domesticus sp. nov. a parasite of nymphs of Periplaneta americana (Linneus, 1758) found in La Plata, Buenos Aires Province, Argentina is described and illustrated. This new species is characterized by having in the mouth a simple stoma with of thick walls, strongly cuticularised forming three pairs of nodules in two rows, without teeth; the excretory pore is located posterior to the beginning of the intestine, the male presents particular distribution of the genital papillae: a pair of big papillae preanal and three pairs of papillae posanales grouped very close, the second pair of papillae are displased a bit laterally, forming with other posanal papillae a circle.